2012
DOI: 10.1108/02632771211252315
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of cognitive failures in open plan offices

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Statistically significant differences in the strength of all types of factors were noted between groups occupying individual, shared and open-plan offices in a recent study by Haynes et al (2017). While limited to a single region, this echoes findings from the broader literature, particularly those relating distraction (negative) and collaboration (positive) to the open-plan office layout (Haynes and Price, 2004; Haynes, 2007; Purdey and Liefer, 2012). While Haynes et al (2017) describe the unilateral impacts of the workplace layout across both open-plan and enclosed office environments, they note that it is the availability and the control over a variety of physical layouts and social interaction points which has the greatest impact on perceived workability.…”
Section: Findings From Literaturesupporting
confidence: 64%
See 2 more Smart Citations
“…Statistically significant differences in the strength of all types of factors were noted between groups occupying individual, shared and open-plan offices in a recent study by Haynes et al (2017). While limited to a single region, this echoes findings from the broader literature, particularly those relating distraction (negative) and collaboration (positive) to the open-plan office layout (Haynes and Price, 2004; Haynes, 2007; Purdey and Liefer, 2012). While Haynes et al (2017) describe the unilateral impacts of the workplace layout across both open-plan and enclosed office environments, they note that it is the availability and the control over a variety of physical layouts and social interaction points which has the greatest impact on perceived workability.…”
Section: Findings From Literaturesupporting
confidence: 64%
“…Market demands are discussed by Haynes (2007a) and can directly impact effectiveness, efficiency, outputs and performance owing to the external requirements imposed for the completion of specific tasks. Similarly, interruptions can affect an individual’s time on task, measured through billable hours and task completion (Wiik, 2011); these are discussed in detail in the context of open-plan office studies such as that by Purdey and Liefer (2012).…”
Section: Findings From Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Bakker (2014) states that the reverse relationship is also true: being productive and attaining one's personal or organisational objectives contributes to satisfaction and well-being. Purdey and Leifer (2012) investigated different types of open plan offices measuring cognitive failures among staff in a local government authority by the use of a computerbased instrument. The open plan offices were different regarding layout, workstations and density and classified as either low or high distraction workspaces.…”
Section: Sustainable Buildingmentioning
confidence: 99%
“…However, the rush to work in open plan came with hidden costswhat we refer to today as productivity costs. Brunia et al (2016) observed that the debate about the pros and cons of open offices is still going on, citing Purdey and Leifer (2012) and Kim and De Dear (2013) as recent examples. According to Chadburn et al 2017, while some research suggests a strong positive link between design and productivity (Gensler, 2005;Myerson et al, 2010;Sullivan et al, 2013), other work is less conclusive (Greene and Myerson, 2011;Thompson and Kay, 2008).…”
Section: The Productive Workplacementioning
confidence: 99%